ANALISIS PUISI “BAHASA LANGIT” KARYA ACEP ZAMZAM NOOR MELALUI PENDEKATAN ALIRAN NEW CRITICISM - Sophia, Ratna; Maulana, Muhammad Fanza; Dzikri, Rifqi Ahmad (Journal of Education for The Language and Literature of Indonesia, 2025)
One form of manifestation of the results of human thought is literary works. Literary works are created, enjoyed, and appreciated by society, and the main purpose of their creation is to be enjoyable. One form of literary work is poetry. Poetry as one of the literary arts has a unique ability to inspire, stir emotions, and convey deep messages to readers or listeners through the use of unique and creative language. One of the poetry works that attracted attention in the Indonesian literary scene was "Bahasa Langit" by Acep Zamzam Noor. This study aims to analyze the poem "Bahasa Langit" by Acep Zamzam Noor using the New Criticism approach. The method used is qualitative content analysis with a focus on analyzing the content of poetry and observing the choice of words used by poets. In addition, the New Criticism approach is used to examine aspects of the content and method of poetry, which include themes, feelings, tones, atmospheres, messages, diction, imagination, concrete words, majas, rhythm, and rhyme. The results of the analysis showed that the poem "Bahasa Langit" contains themes of metaphysics and spirituality, and expresses feelings of joy mixed with tension or anxiety. The poem also conveys the message that language is a means of expressing pent-up feelings and undergoing changes over time. Analysis of the method of the poem "Bahasa Langit" also reveals the use of majas such as metaphor and personification. In the selection of poetic diction and the varied use of majas, this research is expected to contribute to a deeper understanding of this literary work and inspire readers to better appreciate the beauty and complexity of poetry as a form of artistic expression that presents meaning through the play of language and images of the poet.